Factors affecting public trust in government digital services in developing countries: a case of South Africa - Ntika, Nomfezeko (Department of Information Systems, 2026)
Problem Statement: The government in developing countries has been grappling with poor service delivery often evidenced by perpetual destructive service delivery protests. Slow economic growth has further eroded the government capacity to deliver public services effectively and efficiently. The advent of government digital services was intended to address these challenges, hence substantial investment in such initiatives. However, the return on such investment is low due to low uptake of digital services in developing countries. Public trust is the most cited reason for the low uptake of Government digital services. The personal, institutional and technological contextual factors play a pivotal role in building public trust in government digital services. Objective: The objective of the study was to examine and explain how contextual factors affect public trust in Government digital services in developing countries. To achieve this objective, the study analysed how personal, institutional, and technological factors influence public trust in government digital services. Methods This study was of qualitative nature and adopted an interpretive philosophy, a descriptive purpose, and a deductive approach. A conceptual framework was developed based on the literature review. A single case study was adopted. Data were collected through semi-structured interviews. Purposive and snowball sampling techniques were used to select participants. Thematic analysis was used to analyse data. Findings The results of this study show that personal, institutional, and technological contextual factors affect public trust in government digital services. People with low socio-economic status and limited digital efficacy often struggle to access and use these services. Government digital services that are deployed by institutions that lack transparency, accountability and good governance tend to be mistrusted by the public. Additionally, digital services that are not user-friendly, with poor quality of information, and lack adequate data security and privacy further erode public trust. Originality/Contribution: This study made a practical contribution by providing the government with research-based findings that can be used as input in legislation and policies aimed at improving public trust in government digital services. This study also made a theoretical contribution by providing an in-depth analysis of how personal, institutional and technological factors affect public trust in government digital services in developing countries.